2007
DOI: 10.1080/10242420701510668
|View full text |Cite
|
Sign up to set email alerts
|

A generic model for glucose production from various cellulose sources by a commercial cellulase complex

Abstract: The kinetics of cellulose hydrolysis by commercially available Cellubrix were described mathematically, with Avicel and wheat straw as substrates. It was demonstrated that hydrolysis could be described by three reactions: direct glucose formation and indirect glucose formation via cellobiose. Hydrolysis did not involve any soluble oligomers apart from low amounts of cellobiose. Phenomena included in the mathematical model were substrate limitation, adsorption of enzyme onto substrate, glucose inhibition, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
12

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 31 publications
5
39
0
12
Order By: Relevance
“…The rate constant for thermal inactivation is comparable to that reported for T. reesei cellulase enzymes (Drissen et al, 2007). While second-order deactivation has also been reported for T. reesei component enzymes due to aggregation (Dominguez et al, 1992) and loss of synergy (Gusakov et al, 1982), the exponential decrease in residual activity measured here gave R 2 values greater than 0.9, demonstrating that a first-order approximation was sufficient for modeling total enzyme activity in this system.…”
Section: Discussionsupporting
confidence: 77%
“…The rate constant for thermal inactivation is comparable to that reported for T. reesei cellulase enzymes (Drissen et al, 2007). While second-order deactivation has also been reported for T. reesei component enzymes due to aggregation (Dominguez et al, 1992) and loss of synergy (Gusakov et al, 1982), the exponential decrease in residual activity measured here gave R 2 values greater than 0.9, demonstrating that a first-order approximation was sufficient for modeling total enzyme activity in this system.…”
Section: Discussionsupporting
confidence: 77%
“…6). The halflife of EG2 was set to 4.3 h and the half-life of CBH1 was set to 10.6 h. These are much shorter thermal half-life values than the value of the half-life for a commercial T. reesei cellulase mixture reported in the literature, 42.5 h (Drissen et al, 2007).…”
Section: Inclusion Of Thermal Deactivation (Monodisperse Spheres)mentioning
confidence: 99%
“…According to Drissen et al [26], the enzymatic preparation Cellubrix is formed from Celluclast by cellobiase (b-glucosidase) addition. The authors reported a b-glucosidase activity of 204 IU mL À1 of Cellubrix by using cellobiose as substrate for activity determination.…”
Section: Enzymatic Hydrolysis Of Rice Straw Celluligninmentioning
confidence: 99%